A Juridical Review of Civil Sanctions for Fathers Neglecting Child Support Obligations Post-Divorce - Yauma Tertibi (STAI Miftahul Ula Nganjuk, 2026)
This research analyzes the urgency of strengthening civil sanctions against fathers who neglect child support obligations following divorce in Indonesia. Although domestic regulations explicitly mandate fathers to finance their children's needs, the efficacy of court order executions is frequently hindered by the absence of coercive measures. Utilizing a juridical-normative method with a comparative approach, this study finds that the evasion of child maintenance is rooted in weak asset-tracking systems and a lack of integrated administrative sanctions. The novelty of this research lies in the proposed formalization of civil sanctions in the form of automatic wage attachment and restrictions on public service access as instruments of civil coercion. The results indicate that legal restructuring through the integration of population data systems with religious court rulings can significantly enhance paternal compliance. This study recommends a revision of civil procedural law to grant broader executorial authority to judges, thereby ensuring the child's constitutional right to survival and development.